"Neither a wife nor a widow": an interpretative phenomenological analysis of the experiences of female family caregivers in disorders of consciousness. Issue 8 (17th November 2018) - Soeterik, Sonja M.; Connolly, Sarah; Riazi, Afsane
ABSTRACT: Disorders of consciousness (DoC) disrupt close relationships. This study investigated the experience of a DoC in the family. Four main themes were identified from semi-structured interviews with nine females and analysed using Interpretative Phenomenological Analysis (IPA): (1) Loss without a name, (2) Relationship without a title, (3) Symbiotic relating and (4) Frozen futures . Participants' accounts showed complex losses and relationship transformations that were challenging to cope with. Participants embodied the person and experienced reductions in rehabilitation and social visits as personally abandoning and led to strong advocacy with professionals. The uncertainty created by the DoC meant participants lived in the present moment and struggled to make plans for their future. Psychological support to demonstrate a sensitivity and validation of this unique complex loss, a framework for naming the loss, provision of education about the condition and enhancing coping with a chronic situation are needed.